Comparative Anatomical, Histological, and Histochemical Study of the Duodenum between Common Moorhen (Gallinula chloropus) and Domestic Fowl (Gallus domesticus) - Eman Jassem; Adel Hussein; Alaa Sawad (Basrah Journal of Veterinary Research)
This work was designed to conduct an anatomical, histological, and histochemical comparative study of the duodenum between common moorhen and domestic fowl. Thirty birds of common moorhen and thirty birds of domestic fowl that were obtained from a commercial market (Al Basra city) were used in this study, and the work was conducted at the veterinary medicine collage, University of Basra. The anatomical study showed that the duodenum was a convoluted tube that extended as a U shape and held the pancreas between the two arms of the duodenum. The duodenum has similar histological structures in both domestic fowl and common moorhen where the wall of this tubular organ is composed of four layers (tunica mucosa, sub mucosa, muscularis externa, and serosa). The results of statistical analysis revealed significant differences at level P<0.05 in the thickness of (tunica mucosa, crypts, tunica sub mucosa, and tunica muscularis) between two birds. The histochemical study of the duodenum revealed the carbohydrates distribution on the mucous layer and columnar epithelium and around the intestinal glands, while the glycogen granules distribution around the glands and muscle layers.